2021
DOI: 10.1159/000514468
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic Level II Surgical Techniques for Breast Cancer Treatment: Long-Term Outcomes

Abstract: Background: Problems in patients who could not get adequate surgical margins (SM) and good cosmetic results with breast-conserving surgery (BCS) have been overcome with the introduction of oncoplastic surgery (OPS) methods. The purpose of this study was the documentation of level II techniques and the presentation of long-term survival results. Methods: The data on patients who had been prospectively registered in the database between 2007 and 2017 and who had been treated with level II OPS due to invasive bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Considering the evidence in the literature, oncoplastic surgery was found to have low recurrences while improving the cosmetic outcome and patients' quality of life [10,[57][58][59][60][61][62][63][64][65][66][67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the evidence in the literature, oncoplastic surgery was found to have low recurrences while improving the cosmetic outcome and patients' quality of life [10,[57][58][59][60][61][62][63][64][65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the application of oncoplastic techniques has witnessed the emergence of new problems with margin adequacy due to the unavoidable displacement or replacement of residual breast tissue surrounding the excised tumor, according to excision size and location [58][59][60]. Regardless, the current literature demonstrates that oncoplas-tic surgery is a safe option in terms of re-excision, completion mastectomy rates, and local and distant recurrence [10,[61][62][63][64][65][66]; such surgery is oncologically safe and has been recommended in the case of DCIS [67].…”
Section: Evolution Of Margin Acceptabilitymentioning
confidence: 99%
“…Large systematic reviews showed that oncoplastic surgery was more frequently performed in younger patients who required greater breast volume removal for larger tumors ( 23 , 25 , 27 ). While this may not translate to any survival benefit, there could be improvement in patients’ satisfaction rates given the lower rate of reoperation and conversion to mastectomy ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее существуют сложности в оценке онкологической безопасности ОПР по сравнению с классическими радикальными резекциями ввиду невозможности проведения крупных рандомизированных исследований [9]. По данным различных источников частота рецидивов после ОПР достигает 10% [10][11][12][13][14][15].…”
Section: Introductionunclassified